Ownership and uses of human tissue: what are the opinions of surgical in-patients?. Issue 3 (6th February 2008) - Bryant, R J; Harrison, R F; Start, R D; Chetwood, A S A; Chesshire, A M; Reed, M W R; Cross, S S
Abstract : Aims: To investigate whether patient opinion about the uses of tissue removed at therapeutic operations has changed since the adverse publicity surrounding the Alder Hey and Bristol Royal Infirmary Inquiries, and to see whether it aligns with the Human Tissue Act 2004. Methods: A questionnaire was given to 220 postoperative patients in a teaching hospital during an 11 week period. Aggregated responses to each question were ranked in frequency order. Unweighted centroid linkage hierarchical clustering analysis was performed with dendrogram display for the main data on tissue usage. Results: 203 completed questionnaires were collected (compliance rate 92.3%). 96.3% of patients indicated that they would not object to their tissue being used in research, significantly higher than in the 1996 study (89.1%) with no overlap of the 95% CIs. 29.1% of patients believed that the hospital had ownership of tissue once it has been removed during surgery, 23.2% believed they had ownership, 19.7% believed that the pathology laboratory had ownership, and 15.3% believed that nobody had ownership rights in the case of tissue samples. Conclusions: This new survey indicates that despite a turbulent decade for those involved in human tissue retention in the UK, public support for a wide range of human tissue based activities, especially biomedical research, has not diminished and that patient opinion aligns well with the Human Tissue Act 2004.